2006
DOI: 10.1088/0960-1317/16/4/014
|View full text |Cite
|
Sign up to set email alerts
|

The current signal in spark-assisted chemical engraving (SACE): what does it tell us?

Abstract: Spark-assisted chemical engraving (SACE) is a promising micro-machining technology for the low-cost machining of holes and channels in non-conducting materials, such as glass and some ceramics. Despite the complexity of SACE due to the interdependency of thermal, electrochemical and mechanical effects, the key data of the machining process can be obtained from only a few signals. Possible process surveillance signals are analysed and discussed. In particular, the current flowing between the electrodes is analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 39 publications
1
36
2
Order By: Relevance
“…The results indicated deviations in the diameter of the machined contour and the thermal-affected region of approximately 3.7% and 2.7%, respectively. The experimental results indicated good agreement with those obtained by extant studies [ 18 ]. In reference [ 18 ], Wüthrich et al indicated that deviations of the micro-holes with a mean diameter of a few hundred microns typically corresponded to approximately 20% of perfect circular contour.…”
Section: Resultssupporting
confidence: 86%
“…The results indicated deviations in the diameter of the machined contour and the thermal-affected region of approximately 3.7% and 2.7%, respectively. The experimental results indicated good agreement with those obtained by extant studies [ 18 ]. In reference [ 18 ], Wüthrich et al indicated that deviations of the micro-holes with a mean diameter of a few hundred microns typically corresponded to approximately 20% of perfect circular contour.…”
Section: Resultssupporting
confidence: 86%
“…As can be seen from Figure 8, the average current of spark discharge shows a trend to decrease slightly and then increase as the voltage increases. According to the research of Wüthrich et al [27], it is known that in the process of electrochemical When the cathode has loss after 200 s of machining, it can be seen from Figure 7 that the gas film formation time generally shows a decreasing trend, but the reduction is not significant. Zhang et al [26], in their conclusion, stated that the critical voltage also increases with the increase in the diameter of the tool electrode.…”
Section: Average Current Of Spark Dischargementioning
confidence: 98%
“…The trend in the gas film formation time before and after machining is consistent. From another perspective, according to Wüthrich et al [27], the gas film formation time is related to the time required by the local heating of electrolyte, which also depends on the resistance between the electrodes (local temperature of the electrolyte). At high voltages, the spark discharges become more intense, and the conductivity of the electrolyte is enhanced with the increase in the local temperature of the electrolyte, leading to the decrease in resistance between the electrodes.…”
Section: Tool Wearmentioning
confidence: 99%
See 1 more Smart Citation
“…The machining takes place in an electro-chemical cell where the cathode is used as a tool and the anode as a counter-electrode. When a voltage higher than a critical value, called critical voltage, is applied, bubbles grow so dense on the tool electrode that they coalesce into a gas film; this has been identified as one of the key parameters for machining repeatability [3]. Electrical discharges take place between the tool electrode and the electrolyte.…”
Section: Introductionmentioning
confidence: 99%